Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Mitra Usaha Flores - Agustina Nelly Dua Gleko; Maria Silvana Mariabel Carcia; Maria Modesta Missi Mone (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This study aimed to (1) understand the overview of Employee Performance, WorkStress, and Work Environment; and (2) analyze the influence of Work Stress and Work Environment on Employee Performance, both partially and simultaneously. The population of this study consisted of 90 employees at PT.Mitra Usaha Flores. The sampling technique used was simple random sampling, and the sample size was determined using Slovin’s formula, resulting in 48 respondents. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted using F-tests and t-tests. The descriptive analysis results showed that the Employee Performance variable was categorized as good, the Work Stress variable was categorized as good,and the Work Environment variable was also categorized as good. The t-test results indicated that, partially, the work Stress variable (XI) did not affect employee performance. Howewer, the Work Environment variable (X2) significantly affected employee performance. The F-test results showed that, simultaneously, the Work Stress and Work Environment variables together had a significant effect on employee performance. The coefficient of determination analysis showed that the two independent variables in this study explained 9.3% of the variation in employee performance at PT. Mitra Usaha Flores.